Initiator and Photocatalyst‐Free Visible Light Induced One‐Pot Reaction: Concurrent RAFT Polymerization and CuAAC Click Reaction. Issue 9 (30th March 2016) - Wang, Jie; Wang, Xinbo; Xue, Wentao; Chen, Gaojian; Zhang, Weidong; Zhu, Xiulin
Abstract : A new, visible light‐catalyzed, one‐pot and one‐step reaction is successfully employed to design well‐controlled side‐chain functionalized polymers, by the combination of ambient temperature revisible addtion‐fragmentation chain transfer (RAFT) polymerization and click chemistry. Polymerizations are well controlled in a living way under the irradiation of visible light‐emitting diode (LED) light without photocatalyst and initiator, using the trithiocarbonate agent as iniferter (initiator‐transfer agent‐terminator) agent at ambient temperature. Fourier transfer infrared spectroscopy (FT‐IR), NMR, and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) data confirm the successful one‐pot reaction. Compared to the reported zero‐valent metal‐catalyzed one‐pot reaction, the polymerization rate is much faster than that of the click reaction, and the visible light‐catalyzed one‐pot reaction can be freely and easily regulated by turning on and off the light. Abstract : The visible light induced one‐pot reaction is successfully achieved between a clickable monomer and a clickable agent under the irradiation of visible light in the presence of trithiocarbonate agent and CuBr2 /ligand, which avoids the use of initiator and photocatalyst.